Estudo da eletrodeposição da liga Fe-Mo a partir de um banho à base de sorbitol. Caracterização física, química e morfológica dos eletrodepósitos Fe-Mo - Zacarin, Maria Gabriela (Universidade Federal de São Carlos, 2016)
Study of the electrodeposition of Fe-Mo alloy from a sorbitol bath. Physical, Chemical and the morphological characterizations of Fe- Mo eletrodeposits. An alkaline solution for the electrodeposition of Fe-Mo alloys was developed with sorbitol as the complexing agent for Fe(III) ions. The Fe-Mo voltammetric profile showed two cathodic peaks c1 and c2 which were, respectively, associated with the reduction of [Fe(OH)2(sorbitol)2]3- to [Fe(OH)2(sorbitol)2]4- and its further reduction to Fe concomitantly with reduction of Mo oxides/hydroxides to Mo and also with hydrogen evolution reaction (HER) observed by the analysis of voltammetric curves together with the energy-dispersive X-ray spectroscopy (EDS) results. Scanning electron microscopy (SEM) of Fe-Mo electrodeposits with electrodeposition charge density (qd) of 5,30 C cm-2 and 510,20 C cm-2 potentiostatically produced, showed smooth films or with cracks, depending on the deposition potential (Ed). Energy-dispersive X-ray spectroscopy (EDS) analysis of Fe-Mo electrodeposits produced with qd of 5,30 C cm-2 showed that the Mo content varied with Ed from 4,88 wt% (Ed = -1,20 V) to 18,92 wt% (Ed = -1,80 V) and with qd of 510,20 C cm-2 from 25,38 wt% (Ed = -1,60 V) to 37,74 wt% (Ed = -1,40 V). X-ray diffraction (XRD) analysis of the Fe-Mo electrodeposits indicated the presence of Fe3Mo phase independently of Ed and qd values.
Study of the electrodeposition of the Fe-Mo alloy from a sorbitol-based bath. Physical, chemical and morphological characterization of Fe-Mo electrodeposits
Keywords: Eletrodeposição; Liga fe-Mo; Electrodeposition; Fe-Mo alloy; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA